The process of redeveloping waterfront as a public place: efforts towards a more sustainable city - Abdul Latip, Nurul Syala; Shamsuddin, Shuhana (2012)
The process of making Kuala Lumpur waterfront as a public place has taken a long toil. Since the year 1984, the waterfront has been acknowledged to be developed as a public space. More than 25 years had passed since then and it has not been well developed as a public space until today. What has gone wrong? The research aims to find the key reason why the waterfront has not been well implemented as a public space. The research employed a qualitative approach using an in depth interview techniques with the key decision makers for the developments at the waterfront. The findings revealed lack of planning - policies, laws, guidelines, master plan as the main cause on the difficulty of implementation.